A continental view of pine‐associated ectomycorrhizal fungal spore banks: a quiescent functional guild with a strong biogeographic pattern. Issue 4 (3rd January 2015) - Glassman, Sydney I.; Peay, Kabir G.; Talbot, Jennifer M.; Smith, Dylan P.; Chung, Judy A.; Taylor, John W.; Vilgalys, Rytas; Bruns, Thomas D.
Summary: Ecologists have long acknowledged the importance of seed banks; yet, despite the fact that many plants rely on mycorrhizal fungi for survival and growth, the structure of ectomycorrhizal (ECM) fungal spore banks remains poorly understood. The primary goal of this study was to assess the geographic structure in pine‐associated ECM fungal spore banks across the North American continent. Soils were collected from 19 plots in forests across North America. Fresh soils were pyrosequenced for fungal internal transcribed spacer (ITS) amplicons. Adjacent soil cores were dried and bioassayed with pine seedlings, and colonized roots were pyrosequenced to detect resistant propagules of ECM fungi. The results showed that ECM spore banks correlated strongly with biogeographic location, but not with the identity of congeneric plant hosts. Minimal community overlap was found between resident ECM fungi vs those in spore banks, and spore bank assemblages were relatively simple and dominated by Rhizopogon, Wilcoxina, Cenococcum, Thelephora, Tuber, Laccaria and Suillus . Similar to plant seed banks, ECM fungal spore banks are, in general, depauperate, and represent a small and rare subset of the mature forest soil fungal community. Yet, they may be extremely important in fungal colonization after large‐scale disturbances such as clear cuts and forest fires.